2016
DOI: 10.3892/mmr.2016.6090
|View full text |Cite
|
Sign up to set email alerts
|

Safety and toxicology of the intravenous administration of Ang2-siRNA plasmid chitosan magnetic nanoparticles

Abstract: This aim of the present study was to investigate the safety and toxicology of intravenous administration of angiopoietin-2 (Ang2)-small interfering (si)RNA plasmid-chitosan magnetic nanoparticles (CMNPs). Ang2-CMNPs were constructed and subsequently administered at different doses to mice and rats via the tail vein. The acute (in mice) and chronic toxicity (in rats) were observed. The results of the acute toxicity assay revealed that the LD50 mice was >707.0 mg·kg-1·d-1, and the general condition of mice revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Clinical examination of animals did not reveal any behavioral signs of distress or pain following CNP administration. The available published data indicate that both single and multiple intravenous administrations of CNPs and their derivatives at doses similar to ours are tolerated satisfactorily by animals without inducing a change in body weight [25,30,48,59,60]. The absence of differences in the clinical and biochemical blood tests between the groups suggests that the cause of weight loss was not a "classic" cytotoxic effect.…”
Section: Discussionsupporting
confidence: 63%
“…Clinical examination of animals did not reveal any behavioral signs of distress or pain following CNP administration. The available published data indicate that both single and multiple intravenous administrations of CNPs and their derivatives at doses similar to ours are tolerated satisfactorily by animals without inducing a change in body weight [25,30,48,59,60]. The absence of differences in the clinical and biochemical blood tests between the groups suggests that the cause of weight loss was not a "classic" cytotoxic effect.…”
Section: Discussionsupporting
confidence: 63%
“…At the beginning of the study, we selected CS nanoparticles as a delivery vector for 5-FU and siRNA, which has been widely used as gene carrier. 35,36 Following this, an evaluation of the properties of the nanoparticles was conducted, including entrapment efficiency, particle size and zeta potential. The binding efficiency of CS nanoparticles and siRNA was evaluated by agarose gel electrophoresis and the results obtained showed that CS nanoparticles can effectively bind siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the study, we selected CS nanoparticles as a delivery vector for 5-FU and siRNA, which has been widely used as gene carrier 35,36. (A) The accumulation of Rho-123 in cells.…”
mentioning
confidence: 99%
“…Moreover, CS has been reported as a successful nanocarrier of antitumoral drugs . Also, CS coated MNPs have been declared to increase the effect of magnetic hyperthermia in glioblastoma treatment and reducing toxicity in drug delivery to biological systems and gene therapy . Furthermore, since CS has primary amino groups, it can be utilized for controlled drug release, mucoadhesion, in situ gellation, transfection, permeation enhancement, and efflux pump inhibition .…”
Section: Introductionmentioning
confidence: 99%